DAKWAH, TRAFFICKING DAN KDRT - Rahmatiah, ST. (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
Trafficking is recruetment action, carrying, accomodately, sending, moving, or recive someone with hardness intimination. Using hardness, abduction, capture, imitation, swindle, abuse of power or danger posision, wire of debit and credit, for giving purpose or payment, untill get agreement of policymekers on the one else. It is done in the country or country escort, for eksploitation purpose or make someone to be eksploited. Hardness in household is each action to someone specially for woman, who cause appear of miserableor suffer in fisical, sex, psicology, or household neglaction include intimination for doing action, compulsion or seizure of freedom by law resist in household environment.